Buffalo genetic improvement program in Vene- zuela - José A. Aranguren-Méndez; Rafael M. Román-Bravo; Ricardo A. Briceño-Rojas; Mauricio G. Briceño-Rojas; Luis A. Pacheco-Díaz (Revista Científica)
The water buffalo (Bubalus bubalis) has become one of the most important livestock species locally and worldwide, contributing significantly to people’s food security and being a source of milk, meat, leather, manure, horns, and traction power. During the last decades, its inventory has doubled, with a notable improvement in genetics, management, and nutrition practices, coupled with advanced breeding programs, allowing the dissemination and acquisition of improved germplasm. The implementation of genetic evaluations in the water buffalo through Best Linear Unbiased Prediction (BLUP) through the animal model has increased over the last two decades across several countries. This methodology allows the prediction of breeding values (EBVs). It is an integral part of most breeding programs based on two fundamental pillars: phenotypic data (milk production, fat, protein, or morphological traits) and genealogical information (through the availability of a pedigree). Since many of the selection plans in this species have been directed to production traits (milk, solids in milk, and meat), reproduction needs to be included to avoid a reduction in fertility since poor reproductive ability, long age at first calving, calving intervals, and a low conception rate, constituting these elements as one of the main drawbacks of buffalo livestock. Therefore, this research aimed to evaluate the outcome of sixteeen years of an Artificial Insemination (AI) program and develop a selection index that included multiparous females’ milk yield (MY) and reproduction (calving intervals: CI) (60% MY 40% CI) while in the heifers, milk ability and age at first service. This index allows for jointly selecting both important characteristics in buffalo production systems. Moreover, in the American tropics, the crossing of Murrah with the Mediterranean buffalo breed should be avoided since both breeds have a good adaptation to the environment and excellent production levels, which is why an absorption program for the pure breed is recommended in programs for individuals of each breed. The results obtained from the implementation of Artificial Insemination (AI) from 2007 and this index from 2016 to 2023 have allowed us to go from 1445 ± 430 to 1597±415 kg of milk adjusted to 244d and an CI from 420±65.4 to 413±60.7 days. Moreover, the age at the first service of the buffaloes improved from 32.7±10 to 29.7±9.91 months, respectively. The average genetic values of the herd for MY increased from 2.94 to 57.35 kg/lactation, representing a significant increase, and the genetic values for CI improved from -0.02 to -1.12 days, giving indications that it is possible under a selection index, improving both characteristics in buffalo herds in the tropics. Similarly, using proven bulls through Artificial Insemination (AI) for 16 years has shown average improvement values in LA, LA1, LA2, and LA3 animals of 1368.3, 1677.3, and 2083.1 kg/lactation, respectively. In conclusion, genetic improvement programs based on the selection index and the massive use of reproductive biotechnologies are potent tools that must simultaneously accelerate buffalo herds’ genetic progress.